Dança para cavalos: um experimento de escrita - Estaregui, Ana Laura Duarte de Farias (2021)
this work is structured based on a poetic experiment in which an internal logic was sought whose composition could reflect an ordering and not limiting poetics, opening up to a drift in which the text is produced between gaps, in parts, taking into account the elements of chance and intuition. it is a work located in a zone of convergence between poem and process, composed of a body of fragments organized in an analogical way in which notes, images, poems, records about the process, dialogues with authors, etc. are gathered. this formatting, configured around the production of poems, constitutes a kind of diary or report of composition board and seeks to investigate the genealogy of the text through essay exercises, thus proposing to rub some boundaries between writing in process, nature and poem